Development of a German fracture register to assess current fracture care and improve treatment quality: A feasibility study. Issue 12 (December 2017) - Beirer, Marc; Kirchhoff, Chlodwig; Biberthaler, Peter
Abstract : Continuous evaluation of current treatment methods is crucial in orthopaedic trauma surgery. Existing fracture registries substantially contribute to improving fracture care and quality of life in trauma patients. Currently there is no universal German fracture register recording the patient-centred outcome of non-surgical as well as surgical fracture treatment in all anatomical regions. Conclusions regarding nationwide fracture treatment and quality of care are only significant to a limited extent. Cite this article: EFORT Open Rev 2017;2:474–477. DOI: 10.1302/2058-5241.2.160086.